Novel Endoscopic Bariatric Therapies for the Management of Nonalcoholic Steatohepatitis - Gala, Khushboo; Razzak, Farah Abdul; Rapaka, Babusai; Abu Dayyeh, Barham K. (Seminars in Liver Disease, 2022)
Obesity is strongly associated with nonalcoholic fatty liver disease as well as advanced forms of the disease such as nonalcoholic steatohepatitis (NASH), cirrhosis, and hepatocellular carcinoma. While lifestyle and diet modifications have been the cornerstone of treatment for NASH thus far, they are only effective for less than half of the patients. New endoscopic bariatric therapies (EBTs) have already proved to be safe and effective for the treatment of obesity and type 2 diabetes mellitus, and may provide an intermediate, less invasive, cost-effective option for patients with NASH. In this review, we aim to describe the data and evidence as well as outline future areas of development for endobariatric therapies for the treatment of NASH. In conclusion, EBTs present an effective and safe therapeutic modality for use in the growing pandemic of obesity-related liver disease and should be investigated further with large-scale trials in this patient population.
Keywords: endoscopic bariatric and metabolic therapies; weight loss; nonalcoholic steatohepatitis; metabolic effects; obesity